Gene Polymorphisms of Toll-Like Receptor 9 −1486T/C and 2848G/A in Cervical Cancer Risk. Issue 7 (September 2015) - Mu, Xiyan; Zhao, Jitong; Yuan, Xin; Zhao, Xitong; Yao, Kui; Liu, Yingwei; Zhao, Xia
<x xml:space="preserve">Abstract</x> Objective This work aims to explore whether Toll-like receptor 9 (TLR9) −1486T/C and 2848G/A polymorphisms are associated with cervical cancer risk. Methods A comprehensive electronic search of studies published from January 1999 to October 2014 was conducted in Medline (Ovid), Embase, PubMed, Wanfang, Weipu, and CNKI. The algorithm included "TLR, " "Toll-like receptor, " "polymorphism, " "variant, " "mutation, " and "cervical cancer." Seven articles, including 9 studies, were pooled using Revman 5.2 (Cochrane Collaboration, Copenhagen, Denmark). Odds ratio (OR) was used to explore the involvement of minor allele C (C vs T and CC + CT vs TT) of TLR9 (−1486T/C, rs187084) and minor allele A (A vs G and AA + AG vs GG) of TLR9 (2848G/A, rs352140) in cervical cancer risk. Results Toll-like receptor 9 (−1486T/C, rs187084) polymorphisms were associated with an elevated risk of cervical cancer (C vs T: OR, 1.15; 95% confidence interval [CI], 1.03–1.29; CC + CT vs TT: OR, 1.30; 95% CI, 1.11–1.53). We found no significant association between TLR9 (2848G/A, rs352140) polymorphisms and cervical cancer risk (A vs G: OR, 1.15; 95% CI, 0.87–1.54; AA + AG vs GG: OR, 1.27; 95% CI, 0.75–2.17). Conclusions This meta-analysis indicates that TLR9 (−1486T/C, rs187084)—but not TLR9 (2848G/A, rs352140)—may be a risk factor for cervical cancer.